Sustainable Drivers of Financial Success in Nigeria’s Non-Financial Sector: A Managerial Perspective - Adebanjo, Adeleke Abdulyekini; Wisdom, Okere (International Review of Management and Marketing, 2024)
This study examines the determinants of financial performance from a managerial perspective capturing managerial outcomes such as managerial hubris, meetings, risk and compensation. This study utilises the ex post facto methodology. Using a panel ordinary least square regression, the findings demonstrate that a higher frequency of board meetings has a detrimental effect on financial performance, resulting in a 3% decline for each additional meeting. This is a result of an abundance of meetings, mental exhaustion from making too many decisions, and excessive control over tasks and processes. Managerial remuneration has a negative influence on financial performance, resulting in a 21% decline for each unit increase. Nevertheless, despite a substantial 83% decline in performance, management hubris does not have a meaningful impact on financial outcomes. Finally, exercising careful and wise decision-making while taking risks promotes the development of new ideas and the capacity to adjust to new circumstances, resulting in a significant 29% growth. The study's findings indicate that implementing strategic risk management may improve financial performance. This suggests that pay should be in line with long-term goals and that fostering a culture of transparent communication and efficient governance is crucial for minimising adverse effects and fostering sustainable growth outcomes.